Review of text recognition algorothms - Петухова, К. С. (ХНУРЕ, 2019)
This work is created to consider various methods of text recognition on images. The aim of it is to categorize and analyze different algorithms. Text recognition can be defined as main technique for image labeling. In recent years machine learning and pattern recognition, which are useful for text extraction, became very popular in computer vision area. That is why a lot of new schemes and algorithms have appeared. There are a lot of different algorithms and some of them can be useful for one purpose and another for second one. That is why it is important to understand and consider variety of all these approaches and methods.